Три новых рода цестод семейства Echinocotylidae — паразитов птиц - Спасский, А.А. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Вводятся в номенклатуру 3 новых рода паразитов птиц — циклофиллидных цестод семейства Echinocotylidae Ariola, 1899: 1 — Moroshandia Spassky, gen. n.; типовой вид — Moroshandia formosoides (Spasskaya et Spassky, 1961), comb. n.; syn. Microsomacanthus formosoides Spasskaya et Spassky, 1961. 2 — Vladilepis Spassky, gen. n.; типовой вид — Vladilepis cavoarmatus (Sudarikov, 1950). 3 — Mariicotyle Kornyushin, gen. n.; syn. Echinocotyle (Mariicotyle) Kornyushin, 1983; типовой вид — Mariicotyle brachycephala (Creplin, 1829), comb. n.; syn. Taenia brachycephala Creplin, 1829. Приведены родовой и дифференциальный диагнозы этих родов. Three new genera of cyclophillid cestodes from the family Echinocotylidae Ariola, 1899 have been introduced into nomenclature: 1 — Moroshandia Spassky, gen. n.; type species — Moroshandia formosoides (Spasskaya et Spassky, 1961), comb, n.; syn. Microsomacanthus formosoides Spasskaya et Spassky, 1961. 2 — Vladilepis Spassky, gen. n.; type species — Vladilepis cavoarmatus (Sudarikov, 1950). 3 — Mariicotyle Kornyushin, gen. n.; syn. Echinocotyle (Mariicotyle) Kornyushin, 1983; type species — Mariicotyle brachycephala (Creplin, 1829), comb. n.; syn. Taenia brachycephala Creplin, 1829. Bird parasites. Genera diagnoses and differential diagnosis for those genera are given.